Edu-tourist’s perceived service quality and perception – the mediating role of satisfaction from foreign students’ perspectives - Rahman, Muhammad Sabbir; Hassan, Hasliza; Osman-Gani, AAhad M.; Fattah, Fadi Abdel Muniem Abdel; Anwar, Md. Aftab (Emerald Publishing Limited, 2017)
Purpose – The purpose of this paper is to test a conceptual model that takes into account both edu-tourists’ perception and perceived service quality in explaining purchase intention of academic degrees from the foreign universities. Design/methodology/approach – The study is based on an empirical examination with applying multivariate data analysis. The data were collected through survey questionnaires and analysed by using structural equation modelling procedure. Findings – The survey result discovered that the relationship between perceived service quality and edu-tourist’s satisfaction was significant and positive. The relationship between edu-tourist’s satisfaction and intention to purchase was also significant and positive. Meanwhile, edu-tourist’s satisfaction partially mediates the relationship between their perceived service quality and intention to purchase. Nevertheless, this research also explored that the edu-tourist’s satisfaction plays a significant mediating effect in between the relationship of perception and intention to purchase. Research limitations/implications – This empirical study will contribute in understanding the behaviour of international students to construct the theoretical knowledge on the edu-tourism industry, which has been neglected in tourism research. Originality/value – The paper will be of use to the management and policymakers in the higher education sector in understanding the customer’s expectation for the edu-tourism destination. This study contributes to the growing literature on education travel destination, where the researchers investigated the role of tourist’s satisfaction by using perception and perceived service quality towards their intention to visit a destination for education tourism. In addition, understanding the role satisfaction on the relationship between perception and perceived service quality towards the purchase intention will make both scientific and practical contributions for the decision-makers.